“Land of milk and honey”: Ukraine in the work of Manuel Chaves Nogales - Pozo Prado, Juan José; Marchuk, Maryna (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
The work of Spanish journalist Manuel Chaves Nogales contains a significant body of texts addressing the Ukrainian question. Through articles and books written between the 1920s and 1930s, Chaves Nogales expressed his interest and concern for Ukraine within the European context. However, what stands out is not merely the fact that a journalist engages with current affairs, but rather that he goes beyond immediacy and novelty to examine and delve into key aspects of the circumstances he reports on. This study explores the treatment of the Ukrainian theme in Manuel Chaves Nogales’ works, such as "Corresponsal sevillano desde Madrid" (1920-1923), "La vuelta a Europa en avión" (1929), "Lo que ha quedado del Imperio de los zares" (1931), "Otras historias de Ahora" (1932-1936), and "El maestro Juan Martínez que estaba allí" (1934).